The Role of AI in the Recruitment and Human Resource Development Process in Educational Institutions - Chandra Sagul Haratua; Rani Noviyanti; Lusiana Wulansari (Attractive : Innovative Education Journal, 2026)
This study examines the role of Artificial Intelligence (AI) in transforming the recruitment and human resource development processes across various organizations. As the demands for efficiency, objectivity, and quality in human resource management increase, AI offers solutions through automated candidate screening, intelligent matching systems, and personalized professional development platforms.Using a qualitative descriptive method, this research investigates the implementation of AI in several organizations to assess its impact on HR practices. The findings indicate that AI can enhance recruitment efficiency by reducing processing time and minimizing human bias, while also supporting HR development through data-driven training analysis and adaptive learning systems for employees.However, challenges such as data privacy risks, algorithmic bias, technological infrastructure gaps, and limited digital competencies among HR practitioners were also identified. The study concludes that successful AI integration in HR management requires a comprehensive policy framework, continuous capacity building, and ethical oversight to ensure that technology complements, rather than replaces, human judgment. This study contributes to the existing literature by providing a comprehensive qualitative analysis of AI implementation across both recruitment and human resource development functions, highlighting the opportunities and challenges of AI-driven HR practices